Maternal and neonatal tetanus. - Thwaites, C; Beeching, N; Newton, C (Elsevier, 2015)
Maternal and neonatal tetanus is still a substantial but preventable cause of mortality in many developing countries. Case fatality from these diseases remains high and treatment is limited by scarcity of resources and effective drug treatments. The Maternal and Neonatal Tetanus Elimination Initiative, launched by WHO and its partners, has made substantial progress in eliminating maternal and neonatal tetanus. Sustained emphasis on improvement of vaccination coverage, birth hygiene, and surveillance, with specific approaches in high-risk areas, has meant that the incidence of the disease continues to fall. Despite this progress, an estimated 58 000 neonates and an unknown number of mothers die every year from tetanus. As of June, 2014, 24 countries are still to eliminate the disease. Maintenance of elimination needs ongoing vaccination programmes and improved public health infrastructure.